Queijo Minas padrão com baixo teor de sódio e gordura: caracterização físico-química e sensorial - Santis, Valéria Barbosa Gomes de (2016)
The adjunct cultures are widely used for the cheese industry, mainly for its ability to enhance the aroma and flavor of matured cheeses. This study evaluated the effect of application adjunct cultures in cheese standard Minas with low fat content and replacement of sodium chloride by potassium chloride on the physico-chemical and sensory characteristics over 60 days of aging at 14 ° C. Cheeses type standard Mines were made from pasteurized milk with 50% fat reduction, added lactic cultures composed of Lactococcus lactis, Lactococcus cremoris (A) and Lactococcus lactis, Lactococcus cremoris, Lactobacillus helveticus and Streptococcus thermophilus (B), which were salted in different proportions of sodium and potassium chloride, yielding the C treatment (100: 0), T1 (50:50) and T2 (30:70). The physicochemical and sensory analyzes were performed every 20 days old. The sensory evaluation consisted of free technical profile. After 20 days of ripening, cheeses all prepared by formulation B showed to be more moist and greater retention of salt the formulation of the cheese, indicating the functionality of exopolysaccharides formed by the adjunct culture. There was no difference in relation to the fat content and GES. Irrespective of treatment brining, cheese formulation B showed significant increase in the degree of secondary proteolysis reflected in improved sensory quality, since after 20 days of aging showed a greater number of attributes related to aroma and flavor and character texture descriptions positive in view of the reduction of 32% fat level of the cheese. Analysis of formulation A cheese showed delayed action culture as regards the formation of flavors, it took 40 days of aging to mask the bitter and metallic aftertaste arising from changes made. Moreover, over the 60 days of the intensity of the aroma and flavor perception was reduced and the texture-related attributes indicated often a brittle cheese, consistent, dry and crumbly, typical defects caused by the reduction of fat. Thus it can be concluded that the adjunct cultures contributed to the improved texture and flavor in cheese Minas Standard with reduced fat and sodium chloride.